Atypical Chronic Myeloid Leukemia in Pregnancy - Rido Wandrivel; Eifel Faheri; Irza Wahid; Rudy Afriant (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Atypical chronic myeloid leukemia was first depicted as a subtype of myeloid neoplasm that closely resembles chronic myeloid leukemia but does not have the pathognomonic Philadelphia chromosome. Chronic myeloid leukemia can also be found in pregnant and fertile women, which means pregnancy can happen at the time of diagnosis or during the treatment of this disease. Case presentation: A 32-year-old woman came to the hemato-oncology polyclinic at M. Djamil General Hospital Padang with the main complaint of weakness and fatigue. The patient was pregnant with a gestational age of 23-24 weeks. On physical examination, the conjunctiva was anemic, and the spleen was palpable S4 (18 cm). On routine blood laboratory examination, the results of anemia, leukocytosis, and on the peripheral blood picture, severe normochromic normocytic anemia was found with pathological cells of 3% myelocytes and 1% metamyelocytes. Conclusion bone marrow puncture (BMP) results follow the description of chronic myeloid leukemia in the chronic phase. Conclusion: During pregnancy, chronic myeloid leukemia has a better prognosis compared to acute leukemia. However, atypical chronic myeloid leukemia still has the potential of leukostasis, causing uteroplacental deficiency and eventually leading to fetal growth restriction, premature birth, and an increase in perinatal mortality.